Elgar Encyclopedia of Technology and Politics - Ceron, Andrea (Northampton : Edward Elgar Publishing, 2022)
"The Elgar Encyclopedia of Technology and Politics is a landmark resource that offers a comprehensive overview of the ways in which technological development is reshaping politics. Providing an unparalleled starting point for research, it addresses all the major contemporary aspects of the field. Divided into five thematic parts, the Encyclopedia investigates the existing academic literature on the main subfields in this area, before introducing innovative digital research methods. It then highlights the pivotal political and non-political actors leading the process of technological innovation, clarifies key concepts and terms in the field, and finally covers emerging and debated topics. This Encyclopedia will be particularly invaluable for early career researchers and advanced students in politics looking for a concise entry point into any of the various ways in which technology shapes the field. It will also be useful for practitioners to familiarise themselves with the analytical opportunities provided by computational social and political sciences. Key Features: - Entries written by over 90 scholars from 33 different countries on 5 continents - Accessible starting point for research into the key literature, topics and debates in the field - Introduces important new digital methods such as machine learning, text analysis and network analysis - Defines and clarifies the meaning of contested terms such as disinformation, echo chambers and fake news"--
Includes bibliographical references and index.
Keywords: Technology -- Political aspects; Digital media -- Political aspects; Technology and state